The contribution of the Bioágua program to food security and sustainability in the semiarid sections of the Brazilian state of Rio Grande do Norte - Santos, Christiane Fernandes dos; Maia, Zildenice Matias Guedes; Siqueira, Elisabete Stradiotto; Souza, Cimone Rozendo de (Sustainability in Debate, 2016)
In the semiarid sections of the Brazilian state of Rio Grande do Norte the irregular distribution of rainfall is jeopardizes the sustainability and the food security of farmers. Researching sustainability in this region means dealing with the need for optimizing food production through the reuse of water. The present study seeks to evaluate food security and sustainability of families involved in the "Bioágua Familiar" Program. We conducted interviews with four farmers in the Arrimo and Reforma communities, located in the rural municipality of Janduís, state of Rio Grande do Norte. The program's technology increases access to water and allows a constant production of fruit and vegetables for family consumption. However, it was found that the gray water generated is insufficient to maintain the system. The diffusion of this technology depends on a set of strategies that allow people to coexist with semi-aridity. It is concluded that the program on its own is not prone to constitute a sustainable alternative for food production.